The impact of storage conditions on the stability of sugarcane powder biofortified with kefir grains (2015)
The goal of this research project was to assess the quality of sugarcane powder, during storage, that had been biofortified with kefir grains (SP+KG). The powder was obtained by spray drying (SD) sugarcane concentrate that was previously fermented with kefir grains (KG). Maltodextrin, 20% w/w, was used as a drying additive, and high viability of the microbial consortium (lactobacilli, lactococci and yeast) was always sought in order to obtain a functional food enriched with probiotic microorganisms, which facilitate storage and consumption. The product was packed, both vacuum (V) and non-vacuum (WV), and stored at 10, 20 and 30°C for 180 days. The results showed significant differences (p 0.05) in the survival rate of lactobacilli and lactococci for the time, temperature and packaging type (PT) factors; however, the yeast showed no significant differences for the PT factor. For the survival of yeast, lactococci and lactobacilli, the best temperature was 10°C and the best packaging type was V. The survival rates reached with these conditions were 62.82% (yeast), 81.22% (lactococci) and 87.82% (lactobacilli). In addition, the levels attained in terms of physical and chemical properties defined the quality specifications of the product. The sugarcane matrix is an effective vehicle of components with physiological activity such as the microorganisms present in kefir. This qualifies the product as a potential functional food